External shocks and domestic poverty alleviation: simulations with a CGE model of Malawi - Lofgren, Hans; Chulu, Osten; Sichinga, Osky; Simtowe, Franklin; Tchale, Hardwick; Teska, Ralph; Wobst, Peter (International Food Policy Research Institute, 2001)
Two sets of issues loom large on the economic horizon of Malawi: poverty alleviation and the country’s vulnerability to shocks emanating from the outside world. In this paper, simulations with a Computable General Equilibrium (CGE) model of Malawi are used to analyze aspects of these issues. Two types of poverty-alleviating domestic policy shifts are simulated: a public works program and a land reform program. The public works program may function as an absorber of negative shocks elsewhere in the economy. The land reform program may introduce a structural change in the distribution of factor incomes in favor of the poor. The results for the simulated external shocks confirm that Malawi’s economy is highly sensitive to external shocks of the magnitudes that the country has experienced in recent years. The consequences are particularly negative for the non-agricultural population. A more diversified production and export structure would make Malawi less vulnerable to external price shocks and reduce the pressures that lead to sharp exchange rate fluctuations.